Hypoxia-Induced Epithelial-Mesenchymal Transition in Cancers: HIF-1α and Beyond - Tam, Shing Yau; Wu, Vincent W. C.; Law, Helen K. W. (Frontiers in Oncology, 2020)
Metastasis is the main cause of cancer-related mortality. Although the actual process of metastasis remains largely elusive, epithelial-mesenchymal transition (EMT) has been considered as a major event in metastasis. Besides, hypoxia is common in solid cancers and has been considered as an important factor for adverse treatment outcomes including metastasis. Since EMT and hypoxia potentially share several signaling pathways, many recent studies focused on investigate the issue of hypoxia-induced EMT. Among all potential mediators of hypoxia-induced EMT, hypoxia-inducible factor-1α (HIF-1α) has been studied extensively. Moreover, there are other potential mediators that may also contribute to the process. This review aims to summarize the recent reports on hypoxia-induced EMT by HIF-1α or other potential mediators and provide insights for further investigations on this issue. Ultimately, better understanding of hypoxia-induced EMT may allow us to develop anti-metastatic strategies and improve treatment outcomes.